2021
DOI: 10.1017/s0305004121000608
|View full text |Cite
|
Sign up to set email alerts
|

Fourier duality in the Brascamp–Lieb inequality

Abstract: It was observed recently in work of Bez, Buschenhenke, Cowling, Flock and the first author, that the euclidean Brascamp–Lieb inequality satisfies a natural and useful Fourier duality property. The purpose of this paper is to establish an appropriate discrete analogue of this. Our main result identifies the Brascamp–Lieb constants on (finitely-generated) discrete abelian groups with Brascamp–Lieb constants on their (Pontryagin) duals. As will become apparent, the natural setting for this duality principle is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…Furthermore, for torsion-free discrete groups, they showed that if the constant C is finite then it must equal 1 -a conclusion consistent with the classical Young's convolution inequality on the integers. Similar results may be established in the compact setting, and ultimately give rise to an abstract duality principle of the form (2.10) -see [28] for more general conclusions and clarification.…”
Section: 6supporting
confidence: 66%
“…Furthermore, for torsion-free discrete groups, they showed that if the constant C is finite then it must equal 1 -a conclusion consistent with the classical Young's convolution inequality on the integers. Similar results may be established in the compact setting, and ultimately give rise to an abstract duality principle of the form (2.10) -see [28] for more general conclusions and clarification.…”
Section: 6supporting
confidence: 66%